Broad-band analysis of X-ray pulsar 2S 1845–024 - Nabizadeh Armin; Tsygankov Sergey S.; Molkov Sergey V.; Karasev Dmitri I.; Ji Long; Lutovinov Alexander A.; Poutanen Juri (EDP Sciences, 2022)
We present the results of a detailed investigation of the poorly studied X-ray pulsar 2S 1845−024 based on data obtained at the NuSTAR observatory during the type I outburst in 2017. Neither pulse phase-averaged nor phase-resolved spectra of the source show evidence for a cyclotron absorption feature. We also used data obtained from other X-ray observatories (Swift, XMM-Newton and Chandra) to study the spectral properties as a function of orbital phase. The analysis reveals a high hydrogen column density for the source reaching ∼1024 cm−2 around periastron. Using high-quality Chandra data we were able to obtain an accurate localization of 2S 1845−024 at 18h48m16s.8 and Dec. = −2◦25'25".1 (J2000), which allowed us to use infrared (IR) data to roughly classify the optical counterpart of the source as an OB supergiant at a distance of ≳15 kpc.